Quantification of Arbidol by RP-HPLC with photo diode array detection - Angirekula, Narendra (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: A new liquid chromatographic method has been developed for the determination of Arbidol in capsules. Arbidol is the brand name for the anti-viral drug Umifenovir. Umifenovir is used for the treatment for influenza infections. Materials and Methods: SHIMADZU HPLC system with Agilent column (150 mm Ã— 4.6 mm i.d., 3.5 Î¼m particle size) was used for the chromatographic study of Umifenovir on isocratic mode. A mixture of 10 mM tetra butyl ammonium hydrogen sulphate and acetonitrile (50: 50, v/v) was used as mobile phase with flow rate 0.8 mL/min. for the chromatographic separation of Umifenovir. PDA detector was used (UV detection: at 223 nm) and the total run time was 10 mins. Results and Discussion: Umifenovir has obeyed Beer-Lambertâ€™s law 0.5-50 Î¼g/mL with correlation coefficient 0.9999. The LOD and LOQ are found to be 0.1581 Î¼g/mL and 0.4829 Î¼g/mL respectively. Conclusions: The method is simple, precise and accurate and can be used for the determination of Umifenovir. The method was validated as per ICH guidelines.